Nanomaterial Technology and Triple Negative Breast Cancer - Hou, Kai; Ning, Zeng; Chen, Hongbo; Wu, Yiping (Frontiers in Oncology, 2022)
Triple negative breast cancer (TNBC) is a malignant breast cancer subtype that is prone to progression, with high associated metastasis and five-year mortality rates and an overall poor prognosis. Chemotherapy is usually administered to treat TNBC without additional targeted therapies. Novel nanomaterials have a variety of excellent physical and chemical properties and biological functions (including targeting specificity), and contrast agents and drug delivery vectors based on nanotechnology are progressing towards a more accurate and targeted direction. This review discusses the mechanisms of action and prospects for the use of nanotechnology in the treatment of TNBC, thus providing potential new strategies for the diagnosis and treatment of TNBC.